Microbiomic Analysis on Low Abundant Respiratory Biomass Samples; Improved Recovery of Microbial DNA From Bronchoalveolar Lavage Fluid - Saladié, Montserrat; Caparrós-Martín, Jose Antonio; Agudelo-Romero, Patricia; Wark, Peter A. B.; Stick, Stephen M.; O’Gara, Fergal (Frontiers in Microbiology, 2020)
In recent years the study of the commensal microbiota is driving a remarkable paradigm shift in our understanding of human physiology. However, intrinsic technical difficulties associated with investigating the Microbiomics of some body niches are hampering the development of new knowledge. This is particularly the case when investigating the functional role played by the human microbiota in modulating the physiology of key organ systems. A major hurdle in investigating specific Microbiome communities is linked to low bacterial density and susceptibility to bias caused by environmental contamination. To prevent such inaccuracies due to background processing noise, harmonized tools for Microbiomic and bioinformatics practices have been recommended globally. The fact that the impact of this undesirable variability is negatively correlated with the DNA concentration in the sample highlights the necessity to improve existing DNA isolation protocols. In this report, we developed and tested a protocol to more efficiently recover bacterial DNA from low volumes of bronchoalveolar lavage fluid obtained from infants and adults. We have compared the efficiency of the described method with that of a commercially available kit for microbiome analysis in body fluids. We show that this new methodological approach performs better in terms of extraction efficiency. As opposed to commercial kits, the DNA extracts obtained with this new protocol were clearly distinguishable from the negative extraction controls in terms of 16S copy number and Microbiome community profiles. Altogether, we described a cost-efficient protocol that can facilitate microbiome research in low-biomass human niches.